Isolation of Soil Mycoflora of Katao Near Gangtok, India - Sharma*, Kavita (Journal of Phytology, 2010)
Isolation of soil mycoflora from Katao was observed by serial dilution method, In investigation period 146 colonies of 21 fungal species were observed the maximum percentage contribution of Aspergillus fumigatus, A. niger (12.32%), was followed by A. flavus, A. luchensis, Mucor sp. (6.84%) and minimum percentage contribution of Cladosporium sp. (0.68%). The maximum fungal species belongs to the Anamorphic fungi (121 colonies), Zygomycotina (18 Colonies) and mycelia sterilia (white) (7 colonies) were observed.